Talent Scouting Soccer Athletes Aged 10 to 11 Years - Lubis, Ade Evriansyah; Mawardinur; Ratna Dewi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2020)
This study aims to develop a basic skills test model for exploring the talent of prospective KU soccer athletes from 10 to 11 years which is valid and reliable. This research is a research and development that adapts several research steps proposed by Borg & Gall (2007, p.590) as follows: (1) preliminary studies and data collection, (2) planning of research and development processes, (3) product validation , (4) product trials, (5) product revisions, (6) product implementation. Small-scale trials were carried out on 30 tests, and large-scale trials were carried out on 416 tests using cluster sampling techniques. The validity data analysis technique uses Pearson's Product Moment correlations and reliability using the Cronbach’s Alpha test-retest. Z score is used to equalize the unit form. The results of this research and development are in the form of a basic skills test model for talent search for KU soccer athletes from 10 to 11 years old. The test model is appropriate because it is declared valid and reliable, with a calculated value greater than the rtable value. The basic skills test model for talent tracking for KU soccer athletes from 10 to 11 years also produces scoring scales (norms) that are packaged in effective and efficient manuals and tutorials (CDs) and can be used as a guide for trainers on early childhood soccer coaching center in the process of searching for athletes with various levels of giftedness.